PENERAPAN SISTEM REFRIGERASI PADA ALAT PEMBUAT ASAP CAIR UNTUK PENGOPTIMALAN HASIL PRODUKSI - Sumarna, Herlin; ., Haryanto; Hidayati, Baiti; Homzah, Ozkar F (Politeknik Negeri Sriwijaya, Indonesia, 2020)
Recently, liquid smoke is widely used for various needs, both for food purposes and for freezing rubber latex. Liquid smoke began to grow due to the large demand, also using biomass / waste as a base material. Immediate production results are needed by the condensation process. The application of the refrigeration system guides the temperature of the air which is used as a cooling medium in the condensation process during the process of making liquid smoke. This study uses coconut shell as raw material for pyrolysis, and there are 4 temperature variations that are applied in the liquid smoke production process. First without a refrigeration system, the application of a refrigeration system with temperature variations of 22 ° C, 18 ° C and the last one is 15 ° C. The data is taken every 30 minutes for 6 hours. Based on the research results, it was found that the maximum production results using the refrigeration system at an air temperature of 15 ° C, resulted in 375 ml of liquid smoke. Keywords: Liquid Smoke, Refrigeration, Pyrolysis, Coconut Shell